CURRENT CONCEPTS ABOUT THE IMMUNE SYSTEM - Umarova T. A.; Kudratova Z. E.; Pirnazarova U. (Web of Journals Publishing, 2025)
An important role in protecting a person from the aggression of the external environment performs immunity. When an antigen - a foreign agent - enters the body, antibodies begin to be produced in the blood. Antibodies or immunoglobulins are specific proteins that are secreted by B-lymphocytes. Their task is to eliminate exactly that “aggressor” that threatens the body at the moment. This means that they act selectively [1,2,3].
Keywords: Immunity, B-lymphocytes, antibodies, specific proteins, a foreign agent.